Genomes 5 - Brown, T. A. (CRC Press, 2023)
"Genomes 5 is a thoroughly modern textbook about genomes and how they are investigated. In the book techniques come first, then genome anatomies, followed by genome function, and finally genome evolution. The genomes of all types of organism are covered: viruses, bacteria, fungi, plants, and animals including humans"--
Includes bibliographical references and index.
Keywords: Genomes